Well-defined FeP/CdS heterostructure construction with the assistance of amine for the efficient H2 evolution under visible light irradiation. (13th November 2020) - Dou, Ming-Yu; Han, Shu-Rui; Du, Xin-Xin; Pang, Dong-Hui; Li, Lei-Lei
Abstract: The photocatalyst is a crucial factor in determining solar-to-H2 efficiency for solar-driven water splitting. Here, the FeP/CdS well-defined heterostructure was elaborately designed and successfully constructed in-situ to achieve efficient water splitting by using a simple and green solvothermal approach. In the synthetic process, the ethylenediamine plays an important role in the construction of intimate contact interface between FeP and CdS. This good quality FeP/CdS heterostructure can efficiently promote charge separation and transportation, and therefore the charge recombination of CdS was significantly suppressed. As a result, the as-synthesized FeP/CdS heterostructure showed excellent photocatalytic performance under visible-light irradiation with an optimal hydrogen evolution rate of 37.92 mmol g −1 h −1 and an apparent quantum yield of 31.50% at 420 nm far exceeding that of pristine CdS by more than 122 folds. This rate, to the best of our knowledge, outperforms other similar catalytic systems. Graphical abstract: Image 1 Highlights: Well-defined FeP/CdS heterostructure was fabricated with the assistance of amine. Construction and catalytic mechanism of FeP/CdS was detailedly studied. Intimate contact interface contributes to its good performance.